The legal maxims in public finance: A historical and comparative perspective - Abdullah Zawawi, Nur Hana Izzati; Akbar, Mohamed Aslam (International Research Centre of Islamic Economics and Finance (IRCIEF), 2021)
In pursuit of curating the optimal version of a public finance system, governments often rely on a set of maxims that act as a guideline on how they should execute the elements of public finance. In Islamic economics, legal maxims (al-qawa’id al-fiqhiyyah) are very present in public finance as the Islamic legality of government actions must be taken into consideration before any execution. Muslim scholars often propose and create new economic maxims or principles attached to their new economic systems but generally hold the same principles, purposes, and especially sources of Shari’ah in curating the maxims. This is distinct from western maxims as no dogmatic or religious text bind them. Thus, allowing western maxims to be premised on their society’s principles. In the modern context, these two differing systems have been unable to reconcile leading to the inability to practice both western and Islamic systems harmoniously. This paper seeks to propose an integrated approach to both systems through contrasting the maxims of both and identifying the harmonizing elements between the two. Reviewing the prominent ideologies and maxims that have been historically used under these two contexts, i.e., Abu Yusuf, Abu Ubayd, and Adam Smith, David Hume, the work dissects the maxims by discussing the primary sources of these maxims, what they intend to achieve, and how this translates to the systems of public finance suggested by the scholars of both worlds. With the analysis of these maxims, the study expects to trace the beginning of where a public finance system comes from, which translates to applications such as the role of the state, the revenue collections system, and the allocation of these funds. The research concludes with a proposal of an integrated system that leans on the overlapping maxims held by the two public finance systems – a system that assumes a secular government which applies a public finance system that prioritizes public welfare.